2022
DOI: 10.1038/s41598-022-08036-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellobiose phosphorylase from Caldicellulosiruptor bescii catalyzes reversible phosphorolysis via different kinetic mechanisms

Abstract: In the process of yielding biofuels from cellulose degradation, traditional enzymatic hydrolysis, such as β-glucosidase catalyzing cellobiose, can barely resolve the contradiction between cellulose degradation and bioenergy conservation. However, it has been shown that cellobiose phosphorylase provides energetic advantages for cellobiose degradation through a phosphorolytic pathway, which has attracted wide attention. Here, the cellobiose phosphorylase gene from Caldicellulosiruptor bescii (CbCBP) was cloned, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The rate limiting step of cellulase hydrolysis to glucose is β-glucoside hydrolyzes cellobiose into two glucose monomers [ 46 ]. Recently, it has been found that cellobiose phosphorylase can provide energy advantage for Cellobiose degradation through phosphorylation pathway [ 47 ]. The inhibition of cellulase and β-glucosidase activity led to a significant decrease in cellobiose content.…”
Section: Discussionmentioning
confidence: 99%
“…The rate limiting step of cellulase hydrolysis to glucose is β-glucoside hydrolyzes cellobiose into two glucose monomers [ 46 ]. Recently, it has been found that cellobiose phosphorylase can provide energy advantage for Cellobiose degradation through phosphorylation pathway [ 47 ]. The inhibition of cellulase and β-glucosidase activity led to a significant decrease in cellobiose content.…”
Section: Discussionmentioning
confidence: 99%
“…In the past three years, some articles have also reported newly discovered phosphorylases [28][29][30], promising in synthesizing rare sugars. In addition to the one-pot enzymatic preparation method, some articles report phosphorylase cascade reactions to prepare target products [25,[31][32][33].…”
Section: Synthesis Of Nigerose By the Coupling Reaction Of Maltose Ph...mentioning
confidence: 99%